TRENCH FEVER AS WAR INFECTION - Nataliya Vynograd; Zoriana Vasylyshyn; Lyudmyla Kozak; Ihor Chaklosh; Iryna Baidalka; Uliana Shul; Iryna Chaplyk-Chyzho (Acta Medica Leopoliensia)
Trench fever is a bartonellosis disease with a transmissible mechanism transmitted via a specific vector - the human body louse (Pediculus humanus), manifested by a sudden onset, relapsing fever, severe pain in the calf muscles, and abundant maculopapular rash.